Career stability and redirection in adulthood. - Gottfredson, Gary D. (Journal of Applied Psychology, 1977)
Age trends in 5-year career stability and change we examined in an approximately one-in-a-thousand sample of 21to 70-year-old men and women workers. Data on current occupation and occupation five years earlier were collected by the Census Bureau and reorganized for this study using Hollandos occupational classification. Career stability increased with age.for both sexes, and age differences persisted even when the analyses were restricted to occupation clangers or socioeconomically mobile workers. People initially employed in consistant occupations were more stable than those initially employed in inconsistent occupations. Some kinds of mid-career redirection were more common than others. Suggestions for industrial and counseling application and implications for vocational theory are discussed. Tables and neferences are included. (Author/WL)